Containerized Microservices architecture (International Journal of Engineering and Computer Science, 2017)
Microservices are the emerging application platform: It Microservices architecture is not a hype is the architecture that will serve as the basis for many applications over the next few years. to shorten time to market of a software product by improving productivity effect through maximizing the automation in all life circle of the product. Promising container technologies, such as Docker, offer great agility in developing and running applications when combined with microservices-style architecture. Microservices appreciate approaches emerging technologies like DevOps and continuous delivery in terms of software architecture. with MSA style, several important deployment technologies, such as container-based virtualization and container orchestration solutions, have came in to picture. These technologies efficiently exploit cloud platforms, providing a high degree of scalability, availability, and portability for microservices. Despite enough level of performance, there is still a lack of performance engineering approaches explicitly taking into account the particularities of microservices. In this paper, we argue why new solutions to performance engineering for microservices are needed. Furthermore, we identify open issues and outline possible research directions. This paper thoroughly studies microservices architectural design along with the various advantages and disadvantages of containerized microservices, architectural advantages, guide lines, goals and the latest technologies used .